Nickel treatment of soybean seeds: evaluating optimal levels for Bradyrhizobium spp. survival, nitrogen fixation, physiological traits and grain yield - Moretti, Luiz Gustavo; Crusciol, Carlos Alexandre Costa; Nogueira, Marco Antonio; Bossolani, João William; Portugal, José Roberto; Hungria, Mariangela (Frontiers in Plant Science, 2026)
IntroductionAccumulating evidence indicates that fertilizing soybean with nickel (Ni) can enhance biological nitrogen fixation (BNF) and plant productivity. Seed application is ideal for promoting nodule formation and early plant development, but this practice raises the risk of toxicity by reducing the difference between beneficial and harmful doses. Unfortunately, studies of the effects of Ni on the survival of Bradyrhizobium spp. applied as inoculants or on BNF have not yielded a consensus on an optimal dose.MethodsThe objective of this study was to establish Ni thresholds that maximize physiological and productivity benefits for soybean, balancing Ni’s positive effects on BNF and plant growth against risks of phytotoxicity and bacterial inhibition. Soybean seeds were treated with nickel sulfate (NiSO4·6H2O) at six doses: 0, 60, 120, 180, 240, and 300 mg Ni kg−1. We then assessed the effects of seed treatment with Ni on the recovery of Bradyrhizobium cells from treated seeds, BNF as assessed by continuous-flow analysis of acetylene reduction activity (ARA), and soil CO2 evolution in greenhouse experiments. In addition, we evaluated the impact of Ni dose on the physiological, nutritional, agronomic traits, and grain yield of soybean in multi-site field trials over two cropping seasons.Results and DiscussionNi doses of up to 60 mg kg−1 enhanced nitrogenase activity, nodulation, nodule biomass, and grain yield without compromising Bradyrhizobium viability. Doses exceeding this threshold reduced bacterial survival, nodulation, and yield, indicating Ni toxicity. The field trials exhibited a natural gradient in soil Ni levels and texture (0.4–0.6 mg dm−3 sandy to clayey), which helps explain differences in response magnitude and reinforces the need for contextualized recommendations. Applying a second-order polynomial regression to mean standardized Z-scores of integrated agronomic traits revealed a significant quadratic response (p < 0.05). Consequently, an agronomically optimal range of 50–100 mg Ni kg−1 is recommended to sustainably optimize soybean growth and N fixation by balancing the benefits and risks of Ni application.